Classical Guidance Materials on Personal Students Based on INATBKBP Instrument Analysis - Hani Nurrofifah; Muh Farozin (Psychocentrum Review, 2022)
Students need to be able to achieve optimal self-development so personal guidance delivered through classical guidance needs to be considered. However, the material for classical guidance in the personal field that is by the needs of students and can be used as a reference or basis for guidance and counseling teachers is still limited. This study aims to find the right material according to the students' needs for classical personal guidance. The population in this study amounted to 2635 students with a sample of 347 students from 17 junior high schools. Sampling in this study used a simple random sampling technique with the Slowin formula. The research method used is descriptive quantitative using the INATBKBP questionnaire to collect research data. INATBKBP was developed based on Santrock's theory.The 10 material topics obtained become materials, bases, and references that can be used and developed by guidance and counseling teachers in delivering personal guidance through classical guidance to students. These topics are expected to help students to have more awareness and self-acceptance so that they can develop their potential and achieve optimal self-development.